ISOLATION ANTI-DIABETIC AND ANTIOXIDANT EVALUATION OF AQUEOUS EXTRACT OF CANSJERA RHEEDII LEAVES - RAMJITH.U.S; P, ROOPITHA; MATHEW JACOB, CYRIL (Asian Journal of Pharmaceutical and Clinical Research, 2013)
The plant Cansjera rheedii belonging to the family Opiliaceae was selected and various studies such as phytochemical and pharmacological activities were carried out. Plant leaves were collected and was shade dried for 15 days, until it was dry enough for extraction. It was then powdered in a grinder and extracted with solvents such as hexane, ethanol, and water. The extracts were subjected to various preliminary phytochemical tests and the results indicated the presence of flavanoids, in the aqueous extract. The compounds were identified by TLC and isolated by column chromatography. The spectral studies were carried out for the aqueous extract of Cansjera rheedii aquatic leaves and were subjected for purity testing. The purified fractions were subjected to IR (Infra red spectroscopy), 1H NMR(Nuclear Magnetic resonance spectroscopy), MASS Spectroscopy studies for the confirmation of the functional groups, number of protons and molecular weight. The results obtained from the chemical tests, IR, 1HNMR, MASS spectroscopy gave the conclusion that Quercetin-3-O-β-rutinoside was present in the extract. The anti-diabetic activity of the aqueous extract of Cansjera rheedii leaves were compared with that of standard drugs. The aqueous extract of Cansjera rheedii leaves produced significant anti diabetic activity (at doses 200mg/kg and 400mg/kg) in dose dependent manner. The in vitro antioxidant activity was evaluated using DPPH scavenging method At 25, 50, 75, and 100 µg/ml aqueous extracts of Cansjera rheedii was found to produced better (p<0.01) DPPH scavenging activity compared to ethanolic extracts. At 250µg/ml ethanolic extract of Cansjera rheedii was found to have better (p<0.01) DPPH scavenging activity when compared to aqueous extracts of Cansjera rheedii.